Comparative evaluation of shear bond strength of various esthetic restorative materials to dentin: An in vitro study - N Manuja; I K Pandit; N Srivastava; N Gugnani; R Nagpal (Wolters Kluwer Medknow Publications, 2011)
Aim: To comparatively evaluate the shear bond strength of recent tooth-colored restorative materials to dentin. Materials and Methods: Flat dentinal surface were prepared from 60 caries free, extracted human permanent molars and were mounted in acrylic rings. These were randomly divided into four groups - Group A to Group D, according to the restorative material used i.e. Glass ionomer cement (Fuji IX), Giomer (Beautifil), an Ormocer-based composite (Admira) and Nano Ceramic restorative material (Ceram X). These restorative materials were applied on dentinal surface of all the specimens using nylon cylinders. The mounted samples were stored in distilled water for 24 hours and thermocycled. They were then subjected to shear bond strength test using universal testing machine. Data was analyzed using a one-way analysis of variance (ANOVA) and student's 't'-test. Results: Ceram X (16.63±0.94 MPa) and Admira (17.31±0.95 MPa) were comparable in their bond strength values, but depicted significantly higher bond strength when compared to Beautifil (12.39±1.05 MPa) and Fuji IX (7.76±1.07 MPa). Conclusion: Nano-ceramic and ormocer-based restorative materials showed better bonding potential to dentin as compared to GIC and Giomer.